2014
DOI: 10.1002/anie.201402805
|View full text |Cite
|
Sign up to set email alerts
|

Using Soluble Polymers to Enforce Catalyst‐Phase‐Selective Solubility and as Antileaching Agents to Facilitate Homogeneous Catalysis

Abstract: The enforced phase-selective solubility of polyisobutylene (PIB)-bound Rh(II) catalysts in biphasic heptane/acetonitrile mixtures can be used not only to recycle these catalysts but also to minimize bimolecular reactions with ethyl diazoacetate. When cyclopropanation and O-H insertion reactions are carried out with PIB-bound Rh(II) catalysts either with or without addition of an unfunctionalized hydrocarbon polymer cosolvent, dimer by-product formation is suppressed even without slow syringe pump addition of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 17 publications
(9 reference statements)
2
19
0
3
Order By: Relevance
“…Hence, its leaching in water is also negligibly low. Such quantitative phase separation was further demonstrated in our previous studies [25].…”
Section: Introductionsupporting
confidence: 78%
“…Hence, its leaching in water is also negligibly low. Such quantitative phase separation was further demonstrated in our previous studies [25].…”
Section: Introductionsupporting
confidence: 78%
“…To address the issue of insufficient sequestration levels for polar organics, we explored modifying PAO with a PAO‐phase‐anchored cosolvent to generate a sequestering phase that contained molecular‐recognition elements. Our experience with PIB‐bound dyes, ligands, catalysts, and polar nanoparticles is that hydrocarbon oligomeric solvents are very effective at phase‐anchoring PIB‐bound polar species . Thus, we reasoned that a PIB with a hydrogen‐bonding terminal catechol group (Figure ) could be phase‐anchored in PAO and could be used to facilitate sequestration of polar groups in PAO because the ability of catechol to form H‐bonds.…”
Section: Figurementioning
confidence: 99%
“…Our experience with PIB-bound dyes, ligands, catalysts, and polar nanoparticles is that hydrocarbon oligomeric solvents are very effective at phase-anchoring PIB-bound polar species. [9,[16][17][18] Thus, we reasoned that aP IB with ah ydrogen-bonding terminal catecholg roup ( Figure 2) could be phase-anchored in PAOa nd couldb eu sed to facilitate sequestration of polar groups in PAOb ecause the ability of catechol to form H-bonds. This benzene( 900) [a] 7.0 99 hexane (800) [a,d] < 0.1 > 99 benzene( 24) [b] < 0.1 > 99 dichloromethane (1450) [b] 72 95 benzene( 550) [c] 3.4 99 benzene( 450) [d] 8.1 98 1,2-dichloroethane (650) [c] 40 94 1,4-dichlorobenzene (17) [c] < 0.1 > 99 dichloromethane (7000) [c] 350 > 99 THF (11100) [c] 7700 (2820) [e] 30 (76) [e] THF (2820) [c] 330 [e] 88 [e] triethylamine (15 000) [c] 4500 (600) [ [a] Sequestration was performedb ym ixing the D 2 Os olution (3.5 g) containingt he organic impurity with the PAO 432 (1.5 g) with av ortexm ixer for 1min.…”
mentioning
confidence: 99%
“…Our prior work has shown that vinyl-terminated PIB is broadly useful as a precursor for formation of recyclable ligands, catalysts, and reagents that can be easily separated from products. [8][9][10][11][12][13][14] Such separations are effective because terminally functionalized PIB oligomers have excellent phase selective solubility in nonpolar alkanes versus polar solvents like acetonitrile (MeCN), MeOH and water. They are also highly soluble in poly(α-olefin)s (PAOs) like PAO 432 , the fully saturated trimer formed from trimerization of 1-decene.…”
Section: Introductionmentioning
confidence: 99%